2013
DOI: 10.1093/fampra/cmt013
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing and managing anorexia nervosa in UK primary care: a focus group study

Abstract: Overcoming patient repudiation and securing referrals are particular challenges with this patient group. Successfully negotiating these problems appears to require advanced communication skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…In total, 63 papers met the inclusion criteria for the review. 21 83 Table 1 provides the quality assessment scoring of the 63 selected papers and Fig. 1 provides an overview of the selection process as a flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 63 papers met the inclusion criteria for the review. 21 83 Table 1 provides the quality assessment scoring of the 63 selected papers and Fig. 1 provides an overview of the selection process as a flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…A similar small qualitative study of six GPs similarly identified a lack of confidence in GPs interviewed when distinguishing Anorexia Nervosa (AN) from less pathological disordered eating and using a diagnosis of ED rather than AN to ‘label’ patients in some cases (Hunt & Churchill, 2013). …”
Section: Gps Are Not Poor At Identifying the Eds: Nadiamentioning
confidence: 99%
“…In a small qualitative study focusing on AN, GPs highlighted two sides to this process, despite the GP being confident about the patient needing a referral, the difficulties of the patients themselves accepting a referral to specialist care and attending their appointments in specialist care (Hunt & Churchill, 2013). A recent study on care pathways highlighted differences in number of cases of adolescent EDs presenting to secondary/tertiary care per year in areas with specialist ED services or specialist Child and Adolescent Mental Health Services (CAMHS) compared to non-specialist CAMHS, suggesting that GPs might be less likely to refer onwards if they do not have a specialist team available in their area (House et al, 2012).…”
Section: Gps Are Not Poor At Identifying the Eds: Nadiamentioning
confidence: 99%
See 2 more Smart Citations